Student Perceptions of the Use of Android-Based Learning Media in the Production Ecrite Intermediaire Course - Jubliana Sitompul (BIRCU, 2020)
Based on the author's experience, French Language Study Program students have difficulties in learning Wrting at Production Ecrite Intermédiaire course. The author develops an Android-based mobile application as a learning medium to help students learn writing and increase student motivation for independent learning. This study aims to determine the perceptions of French Language study program students about the use of Android-based mobile applications as learning media in the Production Ecrite Intermediare course. This research is in the form of quantitative descriptive research with survey method. The population studied was the 3rd semester students of the French Department of Medan State University who were taking Production Ecrite Intermediare courses in 2019. The sample in this study amounted to 30 people. Data collection is done through the distribution of questionnaires to respondents. The results of this study indicate that students like learning media in the form of mobile applications. This is shown from the results of a survey which stated that 86.% of students had very good perceptions. More specifically, the use of Android based mobile applications as learning media makes students feel motivated to study Production Ecrite Intermediaire independently with a percentage of 86.1% in the agreed category